The SF36 health survey questionnaire: an outcome measure suitable for routine use within the NHS? - Garratt, A M (1993)
OBJECTIVE--To assess the validity, reliability, and acceptability of the short form 36 (SF 36) health survey questionnaire (a shortened version of a battery of 149 health status questions) as a measure of patient outcome in a broad sample of patients suffering from four common clinical conditions. DESIGN--Postal questionnaire, followed up by two reminders at two week intervals. SETTING--Clinics and four training practices in north east Scotland. SUBJECTS--Over 1700 patients aged 16-86 with one of four conditions--low back pain, menorrhagia, suspected peptic ulcer, or varicose veins--and a comparison sample of 900 members of the general population. MAIN OUTCOME MEASURES--The eight scales within the SF36 health profile. RESULTS--The response rate exceeded 75% in the patient population (1310 respondents). The SF36 satisfied rigorous psychometric criteria for validity and internal consistency. Clinical validity was shown by the distinctive profiles generated for each condition, each of which differed from that in the general population in a predictable manner. Furthermore, SF36 scores were lower in referred patients than in patients not referred and were closely related to general practitioners' perceptions of severity. CONCLUSIONS--These results provide support for the SF36 as a potential measure of patient outcome within the NHS. The SF36 seems acceptable to patients, internally consistent, and a valid measure of the health status of a wide range of patients. Before it can be used in the new health service, however, its sensitivity to changes in health status over time must also be tested.